The Effect of Realistic Mathematics Education With Role-Playing Method on Students' Mathematical Representation Ability - Rafiela, Tengku Karina; Andhany, Ella (Universitas Wiralodra, 2023)
The decrease in students' mathematical abilities is caused by students' low interest or motivation in mathematics and the use of teaching approaches that are not suitable for students' learning styles, which is decreasing their interest in learning and struggling to understand mathematical materials. This quantitative study with experimental method aims to find out how influential RME (Realistic Mathematics Education) through role play method is on students' mathematical representation ability. A total of 66 students were positioned as research subjects. Data on students' mathematical representation ability was collected using a test of 5 description questions and analyzed using descriptive statistics in the form of averages and analytical statistics in the form of t-test (Independent Sample Test). The results showed a statistically significant difference between the mathematical representation ability of students who applied RME and students who only applied conventional learning. And if there is a difference then there is an effect of the treatment given to the experimental class. Following up on the findings in this study, RME with role-playing method has a positive effect on students' mathematical representation skills and can be applied in learning mathematics considering that it can encourage students to be actively involved and create a new circumstance in learning.